2003
DOI: 10.1037/0735-7044.117.5.1006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases hippocampal neurogenesis to high levels but does not improve spatial learning in mice bred for increased voluntary wheel running.

Abstract: The hippocampus is important for the acquisition of new memories. It is also one of the few regions in the adult mammalian brain that can generate new nerve cells. The authors tested the hypothesis that voluntary exercise increases neurogenesis and enhances spatial learning in mice selectively bred for high levels of wheel running (S mice). Female S mice and outbred control (C) mice were housed with and without running wheels for 40 days. 5-Bromodeoxyuridine was used to label dividing cells. The Morris water m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
187
4
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(208 citation statements)
references
References 84 publications
13
187
4
4
Order By: Relevance
“…Although individual performances for the entire period varied by up to 20'000 revolutions, even the animal which performed poorest (12'000 revolutions a day), may have surpassed the level necessary for a maximal induction. A ceiling level was also observed in mice selected for high levels of wheel running [50] while a correlation between neurogenesis and performance was present in control outbred Hsd:ICR mice, which typically performed at a much lower level than the C57 mice used in this study.…”
Section: Running For a Rewardmentioning
confidence: 64%
“…Although individual performances for the entire period varied by up to 20'000 revolutions, even the animal which performed poorest (12'000 revolutions a day), may have surpassed the level necessary for a maximal induction. A ceiling level was also observed in mice selected for high levels of wheel running [50] while a correlation between neurogenesis and performance was present in control outbred Hsd:ICR mice, which typically performed at a much lower level than the C57 mice used in this study.…”
Section: Running For a Rewardmentioning
confidence: 64%
“…However, when studying mice instead of rats and applying a different learning task, others showed that the beneficial effects of an enriched environment on cognitive processes do not require an increase in neurogenesis (Meshi et al, 2006). In addition, a study using mice that were selectively bred for high levels of wheel running showed an exercise-induced increase in neurogenesis that reached a plateau level but no corresponding improvement in Morris water maze learning (Rhodes et al, 2003). Thus, additional research will be necessary to determine whether the exercise-induced enhancement of neurogenesis contributes to the positive effects of exercise on Y-maze performance.…”
Section: Exercise Promotes Hippocampal Neurogenesismentioning
confidence: 99%
“…Kolb [78,79] and Rhodes et al [76] found significant differences in the size of brain components in selected mice compared with control mice. Specifically selected mice had significantly larger mid-brain and dentate gyrus volumes compared with control mice [76,78,79], and selected mice had significantly increased non-cerebellar brain masses compared with controls [78,79].…”
Section: (A) Artificial Selection Experimentsmentioning
confidence: 99%
“…Four lines of selected mice voluntarily ran about three times further per day than control lines [73], and this type of selection also increases VO 2,max in these mice [74]. Selected mice had higher BDNF levels following several days of voluntary wheel-running compared with control lines [75], and selected mice showed significantly greater cell genesis in the hippocampus when allowed to run, compared with control mice [76]. In addition, two of the selected mouse lines have significantly higher baseline VEGF levels than control mice, which was correlated with higher muscle capillary density (the other two lines showed a strong trend towards higher VEGF levels than controls, but the difference fell just outside statistical significance; p ÂŒ 0.055) [77].…”
Section: (A) Artificial Selection Experimentsmentioning
confidence: 99%